HbA1c measurement and relationship to incident stroke. Issue 4 (18th January 2016) - Robson, R.; Lacey, A. S.; Luzio, S. D.; Van Woerden, H.; Heaven, M. L.; Wani, M.; Halcox, J. P. J.; Castilla‐Guerra, L.; Dawson, J.; Hewitt, J.
Abstract: Aims: To determine the proportion of people with diabetes who have HbA1c measured, what proportion achieve an HbA1c level of < 58 mmol/mol (7.5%), the frequency of testing and if there was any change in HbA1c level in the year before and the year after an incident stroke. Methods: This study used the Secure Anonymised Information Linkage (SAIL) databank, which stores hospital data for the whole of Wales and ~ 65% of Welsh general practice records, to identify cases of stroke in patients with diabetes between 2000 and 2010. These were matched against patients with diabetes but without stroke disease. We assessed the frequency of HbA1c testing and change in HbA1c in the first year after stroke. Estimation was made of the proportion of patients achieving an HbA1c measurement ≤ 58 mmol/mol (7.5%). Results: There were 1741 patients with diabetes and stroke. Of these, 1173 (67.4%) had their HbA1c checked before their stroke and 1137 (65.3%) after their stroke. In the control group of 16 838 patients with diabetes but no stroke, 8413 (49.9%) and 9288 (55.1%) had their HbA1c checked before and after the case‐matched stroke date, respectively. In patients with diabetes and stroke, HbA1c fell from 61–56 mmol/mol (7.7–7.3%) after their stroke ( P < 0.001). Before the study, 55.0% of patients with stroke had an HbA1c ≥ 58 mmol/mol compared with 65.2% of control patients, these figures were 62.5% and 65.3% after the stroke. Conclusions: The frequency of diabetes testing was higher in patients who had experienced a stroke before and after their incident stroke compared with control patients but did not increase after their stroke. Glucose control improved significantly in the year after a stroke. What's new?: This is the first description of HbA1c assessment in the year before and the year after an incident stroke. The study considers the Secure Anonymized Information Linkage (SAIL) databank, which is a large epidemiological resource, representative of the Welsh population. HbA1c levels were found to decrease in the year after a stroke by 4 mmol/mol (0.4%). Despite falls in HbA1c levels the frequency of HbA1c testing did not change in the year after a stroke.